Vitamin D-binding protein in cervicovaginal fluid as a non-invasive predictor of intra-amniotic infection and impending preterm delivery in women with preterm labor or preterm premature rupture of membranes. - Song Yi Kook; Kyo Hoon Park; Ji Ae Jang; Yu Mi Kim; Hyunsoo Park; Se Jeong Jeon (PLoS ONE, 2018)
Objective To determine whether vitamin D-binding protein (VDBP) in cervicovaginal fluid (CVF) is independently predictive of intra-amniotic infection and imminent spontaneous preterm delivery (SPTD, delivery within 48 hours) in women with preterm labor with intact membranes (PTL) or preterm premature rupture of membranes (PPROM). Method This was a single-center retrospective cohort study. CVF samples for VDBP assays were obtained along with serum C-reactive protein (CRP) levels immediately after amniocentesis in consecutive women with PTL (n = 148) or PPROM (n = 103) between 23.0 and 34.0 weeks of gestation. VDBP levels in CVF were determined by enzyme-linked immunosorbent assay kits. The primary outcome measures were intra-amniotic infection [defined as positive amniotic fluid (AF) culture] and SPTD within 48 hours after sampling. Results In the multivariable analysis, elevated VDBP levels in CVF samples of PTL women were significantly associated with intra-amniotic infection and imminent preterm delivery, even after adjusting for potential confounders (e.g., gestational age at sampling, parity, and serum CRP). However, these relationships were not found in women with PPROM. In women with PTL, the areas under receiver operating characteristic curves of CVF VDBP level for predicting intra-amniotic infection and imminent preterm delivery were 0.66 and 0.71, with cut-off values of 1.76 μg/mL (sensitivity of 64.3% and specificity of 78.4%) and 1.37 μg/mL (sensitivity of 65.4% and specificity of 72.6%), respectively. The CVF VDBP levels were significantly higher in women with PPROM than in those with PTL. Conclusions VDBP in the CVF independently predicts intra-amniotic infection and imminent preterm delivery in women with PTL, whereas in women with PPROM, an elevated VDBP level in CVF is not associated with increased risks of these two outcome variables.